How Long do Your Angiographically Normal Coronary Arteries Remain Normal? A Pilot Study. (March 2015) - Weinstein, Jean Marc; Cafri, Carlos; Kobal, Sergio; Sherf, Michael; Ilia, Reuben
Coronary atherosclerosis is a progressive disease. We sought to determine whether this fact also applies to patients at an advanced age with normal coronary arteries (NCAs) undergoing repeat catheterization at least 5 years later. Of the 189 patients who were found to have NCAs, 154 (81%) remained with NCAs and 35 (19%) developed obstructive coronary artery disease (OCAD). Development of OCAD was observed at all ages. Isolated risk factors were not associated with the appearance of OCAD, but the combination of diabetes mellitus with age >65 years or with smoking was associated with the appearance of OCAD ( P = .04 for both). In conclusion, the finding of angiographically NCAs in elderly individuals does not prevent the later development of OCAD.